General Organization - Parmaxi, Antigoni (My University, 2026)
On the 13th of December 2021 at 12:30 CET we had the third Multiplier Event of the OPENLang Network project in Zoom, organized by the Cyprus University of Technology. The OPENLang Network project aims specifically at developing ‘The OPENLang Network’, which envisages to connect all the Erasmus+ KA1 Mobility Participants (HE students and staff, VET (at least 1 month mobility), Adult and School education staff, Youth learners, Youth Workers, Youth Entrepreneurs) in an OPEN informal and highly interactive online environment which could support more efficiently their effort to develop their language skills of the target mobility EU languages. In parallel, it will support their cultural understanding and integration in the host EU country as well their success in their specific subject field of study and/or work. The event under the title ‘Design, develop and use language materials: The example of language OERs’ aimed to discuss about Language OER, Open Language Education, Erasmus+, Tandem Language Learning. The event also provided information on the work conducted in the OPENLang Network project.